High stability Mn2O3/MnCO3 microcubes synthesized by hydrothermal method for supercapacitor application. (1st June 2022) - Pore, O.C.; Fulari, A.V.; Mujawar, S.H.; Shejwal, R.V.; Fulari, V.J.; Lohar, G.M.
Abstract: Mn2 O3 /MnCO3 microcubes (MCs) are prepared using a hydrothermal method on stainless steel substrate as a current collector by a binder-free approach. The effect of hydrothermal reaction parameters (i.e., reaction time, reaction temperature, and calcination temperature) on structural, morphological, and electrochemical supercapacitor performance of Mn2 O3 /MnCO3 MCs is investigated. The supercapacitor study confirmed that the Mn2 O3 /MnCO3 MCs with reaction time 6 h, reaction temperature 120 °C, and calcination temperature 400 °C exhibits 265.7 F g −1 specific capacitance at 0.4 mA cm −2 current density. In addition, it offers excellent capacity retention of 111.1% after 10000 galvanostatic charge-discharge cycles. Such low-cost synthesis, excellent cyclic stability MCs are favorable for energy storage devices. Graphical abstract: Image 1 Highlights: A simple and cost-effective hydrothermal technique is used for fabrication of Mn2 O3 /MnCO3 microcubes. Binder free preparation of Mn2 O3 /MnCO3 microcubes on cost-effective stainless-steel substrate. The Mn2 O3 /MnCO3 electrode shows excellent supercapacitive properties. The Mn2 O3 /MnCO3 shows outstanding capacity retention.